2008
DOI: 10.1007/s00520-008-0472-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of nutrition impact symptoms and their relationship to quality of life and clinical outcomes in medical oncology patients

Abstract: Nutrition impact symptoms were commonly experienced, even 12 months following commencement of chemotherapy, and were associated with poorer QoL and performance status. This highlights the importance of early identification and management of nutrition impact symptoms with adequate follow-up in order to provide optimal care for people with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 23 publications
3
108
0
13
Order By: Relevance
“…Especially fatigue, oral dryness and pain at rest seemed to affect EI negatively. The findings were consistent with our hypothesis and are in accordance with studies suggesting that patients with weight loss experience symptoms that may affect their EI [29,26]. To our knowledge, this is the first direct comparison between actual EI intake and symptom intensity in patients with PC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Especially fatigue, oral dryness and pain at rest seemed to affect EI negatively. The findings were consistent with our hypothesis and are in accordance with studies suggesting that patients with weight loss experience symptoms that may affect their EI [29,26]. To our knowledge, this is the first direct comparison between actual EI intake and symptom intensity in patients with PC.…”
Section: Discussionsupporting
confidence: 92%
“…The QLQ-PAN26 includes 26 items covering symptoms related to PC and its treatment (pancreatic pain, dietary changes, altered bowel habits, indigestion, flatulence, oral dryness, taste changes, cachexia and jaundice) as well as emotional problems (body image, fear of future health, healthcare satisfaction and sexuality) [23]. For this study we only used the eight items/scales covering symptoms most likely to influence dietary intake; pancreatic pain, dietary changes, altered bowel habits, indigestion, flatulence, oral dryness, taste changes and cachexia [25,26]. All items have the following four-answer categories, "not at all," "a little," "quite a bit," or "very much" that were converted to 0-100 scales according to the EORTC methodology [27].…”
Section: Symptom Assessmentmentioning
confidence: 99%
“…The radiation reaction is also prone to cause damage of the salivary glands, reduce salivation, saliva become viscous, and the patient can have chewing and swallowing difficulties. Radiation damage may improve over months and some may never return to the level prior to treatment (24). During the course of treatment, patients also appear nausea and vomiting, anorexic, with full bilge, diarrhea, catarrh, stomatitis, pain and other symptoms (25).…”
Section: Discussionmentioning
confidence: 99%
“…1 Some studies have reported that nutritional risk tends to worsen during the course of admission and has been associated with increased morbidity and mortality, prolonged hospital stay and increased health-care costs in the patients with cancer. 1,2 The value of nutritional support for patients with cancer is to improve the clinical outcomes. 3 Our multicenter prospective cohort study has showed that of the patients at nutritional risk, the complication rate was significantly lower in the nutritional-support group than in the no-support group, and multivariate analysis showed nutritional support was a protective factor for complications in at-risk patients when adjusted for confounders.…”
Section: Introductionmentioning
confidence: 99%